Assessing patient and caregiver satisfaction with outpatient palliative care telemedicine service at a tertiary care hospital in Karachi, Pakistan - Ismat Jabeen; Asra Qureshi; Sidra Assad; Uqba Qamar; Muhammad Atif Waqar (Pakistan Journal of Medical Sciences, 2026)
Background and Objectives: Telemedicine has been identified as a valuable tool to enhance access to palliative care (PC) for patients with serious illness. It is crucial in addressing access barrier resulting from a shortage of trained professionals and specialized services. However, effectiveness of telemedicine in PC setting remains under-evaluated, highlighting the need for further research to assess its impact and optimize its use. We aimed to evaluate patient satisfaction with telemedicine appointment system and PC team during virtual outpatient PC telemedicine consultation. Methodology: This cross-sectional study was conducted on patients recruited through convenience sampling who attended adult PC telemedicine clinics between February 2020-March 2022 at a tertiary care hospital. Patient satisfaction was measured using a self-designed, structured, and pretested questionnaire. Descriptive analysis was performed on all database entries. Results: A total of 130 patients participated with a mean age of 63.2±12.7 years, 47% were male and 53% were female. There were 58% initial visits and 41% follow-ups. 94% of participants agreed with healthcare access, 92% with quality of care, 92% with patient-physician interaction, 77% with convenience, 91% wanted to continue teleconsultation and 88% found it cost-effective. Besides this, 46% of participants expressed concerns about potential privacy breach. Conclusion: Telemedicine is an innovative approach. Participants find it accessible, cost-effective, convenient and of good quality. In future, it should be promoted in post-pandemic landscape as an effective patient care modality to address enormous unmet needs of patients with functional frailty or living in remote area.